Association between Noise Exposure and Quality of Life among People Living Near Stone-Mortar Factories, Phayao Province, Northern Thailand: 10.32526/ennrj/19/2020050 - Thongtip, Sakesun; Sangkham, Sarawut; Srivichai, Piyavadee; Vongruang, Patipat (Environment and Natural Resources Journal, 2021)
Noise may have adverse effects on health and quality of life (QoL). This study assessed the association between noise exposure and QoL among people living near stone-mortar factories. A cross-sectional descriptive study was conducted using 269 subjects. The data was collected using questionnaires, sound level meter, and a geographic information system technique. The statistical analysis was carried out using independent t-test, ANOVA, Pearson’s correlation coefficient test and multiple binary logistic regression analysis. The average noise in factory no. 2, 4, and 5 was found to be higher than the standard level of NIOSH at 85 dB(A) and OSHA at 90 dB(A) for an 8-hour TWA. The multiple binary logistic regression analysis showed that an increasing residential distance was associated with high noise exposure after adjusting for age, education, income, length of stay in community, and overall QoL. The local policy makers should be required to emphasize on the reduction of noise pollution in stone-mortar factories and health surveillance of the residential neighborhood.